Grief Dreams in Traumatic Grief Counseling and Attachment Informed Grief Therapy (Sains Humanika, 2025)
Bereavement and grief, particularly following natural disasters, can evoke a variety of painful emotions, including sadness and guilt. For some, particularly after a traumatic loss, the grieving process can become complicated, leading to significant distress. This paper explores the therapeutic function of grief dreams—dreams in which the deceased appears—as a tool for processing loss. Using a pragmatic case study approach, this article analyzes dream reports through Grief Counseling, and Attachment Informed Grief Therapy on 3 cases, five perspectives that allow us to sincerely mourn the death of the deceased and hold it in our mind, rather than stirring up anxiety, fear, and despair about our own death. 1. Dreams as a Venue for Symbolic Reunion. 2. Dreams as a Reflection of Acceptance 3. Dreams as a Means of Re-experiencing Trauma 4. The Resolution of Grief Dreams as a Marker of Progress 5. Sadness is a bond with the deceased.
Keywords: Greif dreams, bereavement, Grief Counseling, Attachment-Informed Greif Therapy, Case Study